CURRENT SITUATION AND PROGRESS OF PROCEDURE OF BANKRUPTCY OF PHYSICAL PERSONS TRENDS IN REPUBLIC OF KAZAKHSTAN - Eleusizova Индира Каржаубаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In the article given it a shoot an author opening of substantive provisions of procedure of bankruptcy of physical persons, a current situation is including analysed, foreign experience and on the basis of that done suggestions on introduction of institute of bankruptcy of physical persons in Republic of Kazakhstan.